Efektivitas Teknik Point-Counterpoint Berbantuan Media Kartu Pada Pembelajaran IPS Kelas 5 di SDN 1 Satui Timur - Raudatul Jannah; Khairunnisa (Jurnal Pendidikan Dasar Islam, 2024)
The objectives of this study were to measure the learning outcomes of students using the point-counterpoint technique assisted by card media in social science learning at SDN 1 Satui Timur, and to see the effectiveness of the point-counterpoint technique using card media in social studies learning. This study used an experimental method with a research design using the One-Group Pretest-Posttest model. The population in this study were 5A grade students at SDN 1 Satui Timur totaling 13 people, and sampling using saturated sample technique. Data collection techniques using test and observation instruments, then the data were analyzed using descriptive statistical data analysis techniques, normality tests and paired sample t-test using SPSS version 24. Students' learning outcomes in science studies learning after using point-counterpoint techniques assisted by card are included in the predicate 'Enough' seen in the average student learning outcomes of 65.08. In the paired sample t-test test results, the significance (2-tailed) 0.000 <0.005 is obtained, which means that H0 is rejected and Ha is accepted, meaning that the point-counterpoint technique assisted by card is effectively used in social science learning in class 5A at SDN 1 Satui Timur